Analysis of pre-monsoon thunderstorm frequency over Srlniketan, Alipore and Kalaikunda -The possible association with solar activity - KAR, INDRANI; BONDYOPADHAYA, R. (MAUSAM, 1996)
ABSTRACT -General characteristic features of thunderstorm frequency (TSF) observed during (1951-89) during pre-monsoon season at Sriniketan (23°39'N, 87"42'E), Alipore (22° 32'N, 88"20'E) and Kalaikunda (21°20'N, 87" 13'E) have been studied. It is seen that premonsoon TSF follows a rough periodicity 0f 6.6) year. For Kalaikunda (KLK) there is an overal1 upward trend and for Sriniketan (SKT) an overall downward trend; whereas, for Alipore (ALP) the trend pattern remains practically constant. The maximum TSF attained by all these three stations is nearly twice that of mean TSF of respective stations. The solar influence on the frequency of thunderstorm (TS) has been investigated and found to be interesting. TSF over SKT and KLK attained minimum value while that over ALP was near minimum during 1957; which in turn was the year of maximum sunspot (SS) number over the entire period of analysis. Now in general, if we take SS number and TSF of same year and calculate correlation coefficient (CC) considering all the years. i.e., taking SS without any restriction, the CC comes out to be quite small. But the result is just the reverse when the TSF value of those years is considered when SS number is higher. In particular when SS number exceeds some critical value (~140), TSF decreases sharply. The effect of solar sub-cycle, 11-yearcycle and 22-yearcycle un TS has also been discussed. It is seen that during min-max sub-phases, mean TSF is comparatively higher than its value in neighbouring max-min sub-phases and also it is in opposite phase in relation with mean SS. During 11-yearcycle also in most of the cases an opposite phase relationship exists between mean TSF and mean SS.